Suicide attempts and mental disorders - Albis Yomaira Pabon Basto (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Suicide is a serious global public health problem.  More than 800,000 people commit suicide every year and between 10 and 20 million people attempt suicide annually. Suicide has been considered a preventable behavior and suicide attempt is a clinically relevant predictor which is present in one-third of consummated suicides.  Besides, having a mental disorder is another risk factor for suicide. Objective: To determine the relationship between suicide attempts and mental disorders such as depressive and anxiety disorders, bipolar disorder, substance-related disorders, schizophrenia and other psychotic disorders, personality disorders, and eating disorders. Material and Methods: A search was performed in Dialnet, Redalyc, Scielo, Virtual Health Library (VHL), PubMed, Science Direct, and Google Scholar databases in Spanish and English.  It was limited to publications between January 1, 2010 and December 31, 2020. Development: The lifetime prevalence of suicide attempt is 31% in patients with Bipolar Disorder; 33,9 % in patients with Major Depressive Disorder and 26.8% in patients with Schizophrenia. Conclusions: Patients with bipolar disorder and major depressive disorder have higher rates of suicide attempts. Coupled with psychiatric comorbidity (alcohol consumption, smoking, borderline personality disorder), more previous suicide attempts increase the risk of suicidal behavior.